External Factors Triggering Speaking Anxiety In The Academic Setting - Misnariah Idrus (Universitas Negeri Makassar, 2022)
Abstract. In a number of English classes I have taught, a common phenomenon I found is that most students were silent during the class. Even when they are instructured to talk, they are often hestitant to start. A potential factor leading to the phenomena is the existence of speaking anxiety. The aim of this research is to unfold external factors promoting speaking anxiety among EFL Learners in an Indonesian university. I employed a qualitative case study and purposively invited thirty EFL students who I found hesitant to talk in my class although they got a good score in the speaking test. Data to answer the research question were gathered through reflective journal, focus group discussion, and interviews. Data were coded and grouped before I withdrew a conclusion. I concluded that there are five external conditions which are believed promoting the students speaking anxiety consisting of the politeness norm of students’ cultural background, the inability to speak English with someone sharing similar first language, the Indonesian students’ cultural belief that teacher is the person who knows everything about the subject, the students’ need to maintain their positive face and feeling afraid for decreasing or losing the speaking partner’s positive face through inappropriate joke. Keywords : EFL, Speaking, anxiety, external factors